Flow-diverter stents combined with flow-T stenting-assisted coiling for the treatment of a large basilar apex aneurysm: a case report with a 9-month follow-up - Wang, Hao; Zhang, Jingyu; Yang, Huajiang; Zeng, Shi; Guo, Tengyun; Xu, Lunshan; Yang, Donghong (Frontiers in Neurology, 2024)
Background Endovascular or surgical treatment of wide-neck, large basilar apex aneurysms is challenging. We present a novel concept for the treatment of complex basilar apex aneurysms using flow-diverter devices combined with the flow-T stenting-assisted coiling technique. Assess the efficacy and safety profile of the technique in this complex aneurysm. Case description A patient with multiple unruptured intracranial aneurysms underwent staged treatment. A large basilar apex aneurysm was treated with a flow-diverter stent combined with a flow-T stenting-assisted coiling technique in the first stage, and a giant supraclinoid aneurysm was treated with a flow-diverter stent applied in the second stage. Clinical presentations, technical details, intra- and perioperative complications, and clinical and angiographic outcomes were recorded, with a 9-month follow-up. Results The patient achieved full neurologic recovery postoperatively. Cerebral angiography performed postoperatively showed revascularization, good laminar flow, and no in-stent or adjacent stenosis. Conclusion Flow-diverter stents combined with flow-T stenting-assisted coiling for the treatment of giant basilar apex aneurysms is a feasible technique with efficacy demonstrated at a 9-month follow-up. Staged endovascular treatment of multiple intracranial aneurysms may be a safe and viable option.